2005
DOI: 10.1007/s00508-005-0394-z
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels of polyunsaturated fatty acids in children with atopic dermatitis and in atopic and nonatopic controls

Abstract: Dysregulation of n-6 PUFA metabolism is neither consistently found in nor specifically associated with atopic dermatitis but rather appears to be associated with IgE production and atopy in general. The finding of decreased GLA levels in eczema patients with elevated total IgE and in children with allergic rhinitis and asthma but not in eczema patients with normal total IgE questions the proposed pathophysiologic role of fatty acid dysregulation in atopic dermatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…While recently, IgE levels in both children and adults with atopic eczema were shown to be significantly higher than in controls [49]. In addition, its direct association with lower than normal GLA levels has implied that abnormal fatty acid metabolism is part of the atopic condition [50]. This study showed that children with atopic conditions including eczema, rhinitis and asthma without eczema and high IgE, have low GLA compared with children that have non-atopic eczema and low IgE or non-atopic children.…”
Section: Speculative Debatementioning
confidence: 97%
“…While recently, IgE levels in both children and adults with atopic eczema were shown to be significantly higher than in controls [49]. In addition, its direct association with lower than normal GLA levels has implied that abnormal fatty acid metabolism is part of the atopic condition [50]. This study showed that children with atopic conditions including eczema, rhinitis and asthma without eczema and high IgE, have low GLA compared with children that have non-atopic eczema and low IgE or non-atopic children.…”
Section: Speculative Debatementioning
confidence: 97%
“…Thus, low GLA levels might contribute to inflammation of allergic diseases. Accordingly, GLA levels inversely correlated with total serum IgE levels [18]. It has been shown that in children with AD receiving GLA supplementation have a lower SCORAD compared to the placebo group [19].…”
Section: Discussionmentioning
confidence: 94%
“…The predominating expression of a Th1 or Th2-like cytokine pattern can be modulated by numerous eicosanoids and cytokines which are synthesized by antigen presenting cells in the vicinity of the Th0 cell (Romagnani 2004). For example, prostaglandin E 2 (PGE 2 ) secreting antigen presenting cells can switch the Th0 cell to an increased synthesis of IL-10 and a decreased synthesis of IL-12, and hence towards a rather Th2-like pattern (Gold et al 1994). A second approach uses the proliferative response of cord blood lymphocytes to allergens as a measure of allergy risk.…”
Section: Allergy and Immune Developmentmentioning
confidence: 99%
“…Another study found decreased levels of omega-6 LC-PUFA AA in the milk of atopic mothers, which could not be elevated by supplementation of the AA precursor DHGLA (Thijs et al 2000), compared to non-atopic mothers. This could be explained by an impairment of enzymatic activity, not only in Δ6-desaturase, but probably also in Δ5-desaturase in atopic mothers (Focke et al 2005, Schaeffer et al 2006). In contrast, both Laiho et al (2003) and Stoney et al (2004) found no differences in the breast milk fatty acid profi le from atopic and non atopic mothers.…”
Section: Composition Of Breast Milk -Fatty Acidsmentioning
confidence: 99%